2008
DOI: 10.1063/1.2939556
|View full text |Cite
|
Sign up to set email alerts
|

Polarization enhancement for poly(vinylidene fluoride-trifluoroethylene) 75∕25 copolymer films by interlayer ordering under cyclic electric field

Abstract: We report an intriguing phenomenon of polarization enhancement for poly(vinylidene fluoride-trifluoroethylene) 75∕25mol% copolymer films under cyclic electric field. If the copolymer film is initially subjected to electric cycling at a comparatively low field magnitude, the remanent polarization (Pr) increases with the field cycles during the subsequent electric cycling at a higher field magnitude. The morphology and microstructure change during the electric cycling are examined. It is suggested that polymer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 14 publications
4
36
0
Order By: Relevance
“…The polarization enhancement has been observed previously, where it was reported that it might be due to field-induced recrystallization16. We note that a similar enhancement can be found, upon close inspection, in other reported data sets, both for organic1718 and inorganic ferroelectrics2. In all our measurements there is an apparent correlation between the polarization enhancement and the onset of degradation.…”
Section: Resultssupporting
confidence: 91%
“…The polarization enhancement has been observed previously, where it was reported that it might be due to field-induced recrystallization16. We note that a similar enhancement can be found, upon close inspection, in other reported data sets, both for organic1718 and inorganic ferroelectrics2. In all our measurements there is an apparent correlation between the polarization enhancement and the onset of degradation.…”
Section: Resultssupporting
confidence: 91%
“…Similar to that reported in Ref. for P(VDF‐TrEF) 75/25, copolymer of P(VDF‐TrFE) 65/35 also shows the polarization enhancement under the tailored electric cycling. When electric cycling at a lower field magnitude of 70 MV/m, there are hardly any changes for P r , P s , and E c after electric cycling for 30,000 cycles.…”
Section: Resultssupporting
confidence: 88%
“…When electric cycling at a lower field magnitude of 70 MV/m, there are hardly any changes for P r , P s , and E c after electric cycling for 30,000 cycles. The value of the lower filed magnitude is chosen to be over the coercive field and the obtained polarization loop is comparatively slim . Therefore, upon the electric field cycling, there is an increase for the dipole or molecular chain ordering, while the electric cycling would not cause much damage to the film samples …”
Section: Resultsmentioning
confidence: 99%
“…Poly(vinylidene fluoride-trifluoroethylene) [P(VDF-TrFE)] copolymer is one of the promising materials to fulfill both properties at once [7,8]. There have been many reports on the memory characteristics of P(VDF-TrFE) with metal-ferroelectric-metal (MFM) [9][10][11], metal-ferroelectric-insulator-semiconductor (MFIS) capacitors, or OFETs [12][13][14][15][16][17][18]. Although these results clearly suggest a high feasibility of P(VDF-TrFE) for nonvolatile memory, there are a few challenges must be addressed such as a high programming voltage, low switching speed, and insufficient data retention time and various approaches including modifications of material and/or device structure have been proposed [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%